Ichthyofauna Diversity in Danau Teluk: Analysis Using Gill Nets and Lift Nets - Purba, Citra Amelia; Suprayogi, Dawam; Wulandari, Tia (Universitas Jambi, 2024)
This study aims to explore and document the ichthyofauna diversity in the waters of Teluk Lake, Jambi City, using gill nets and lift nets. Sampling was conducted at three research stations from April to June 2024. Environmental physical and chemical factors such as temperature, pH, and water clarity were measured to understand their impact on the fish community. The results showed that the water temperature at stations I and II was 29°C, while at station III, it was 28°C. The pH values ranged from 6.41 to 6.95, and water clarity ranged from 7 to 21 cm. A total of 218 individual fish from 17 species and 8 families were found, with the Cyprinidae family being the dominant group. The Shannon-Wiener diversity index (H') ranged from 0.94 to 2.01, indicating moderate to high diversity. The evenness index (E) ranged from 0.58 to 0.91, indicating relatively even distribution of individuals. The dominance index (C) ranged from 0.14 to 0.53, indicating no species significantly dominated the community.